Principal Leadership as a Construction of Teacher Work Culture - Ahmad Soadikin; Syamsul Huda Rohmadi (FiTUA: JURNAL STUDI ISLAM, 2026)
This study aims to analyze how the leadership of school principals in building the work culture of phenomenological studies teachers in Indonesian junior high schools. The research method uses a qualitative approach with a Husserlian transcendental phenomenological design of data collection techniques carried out by observation, interviewing and documenting 47 informants purposively, then analyzed using three thematic isolation techniques (holistic, selective, in-depth). The validity of the data is guaranteed through triangulation, member checking, and bracketing. The results show that the meaning of leadership has metamorphosed from an administrative manager to a performative moral role model and a transformative agent. The institutionalization of work culture forms a stable habitus through the mechanism of behavioral enculturation, ritualistic internalization, and habituation structuring. From a teacher's perspective, a positive work culture is catalyzed by relational-distributive leadership, procedural fairness, and psychological safe spaces. However, its optimization in the field is hampered by bureaucratic constraints (administrative overload), resistance of senior teachers, and limited infrastructure, which is contrary to supporting factors such as the positive quality of the Leader-Member Exchange (LMX) relationship.